1999
DOI: 10.1007/s11743-999-0066-7
|View full text |Cite
|
Sign up to set email alerts
|

Nonsolvent quantitation of anionic surfactants and other inorganic ingredients in laundry detergent products by X‐ray fluorescence spectrometry

Abstract: This paper reports the development of a method for measuring alkyl-benzene sulfonates, alkyl sulfates, and other inorganic ingredients in laundry detergent products without requiring the use of chlorinated organic solvents such as chloroform. Zeolite is first filtered as a residue on filter paper from an aqueous detergent solution. A calcium solution is then added to the filtrate. Alkyl-benzene sulfonates, alkyl sulfates, and phosphate are precipitated as calcium salts and recovered as residues via filtration.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2000
2000

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Morel and colleagues 440 evaluated methods for measurement of uranium enrichment by recording emissions from 235 U, 238 U and X-ray ¯uorescence induced within the sample by radiation w100 keV. And ®nally, the role of several techniques, including XRF, in characterizing plutonium for the purposes of international security, stock-pile stewardship and the characterization of mixed oxide fuels were discussed in a conference presentation by Mahan et al 441 XRF has also contributed to an astonishing variety of other industrial applications including: the analysis of drugs; 442 cigarettes widely smoked in Kenya and cigarette ash 443 in which it was reported that signi®cant quantities of As, Ga and Se were ingested during smoking; beauty creams also sold in Kenya, 444 where concern was expressed about the Hg content of some of the samples; anionic surfactants and other inorganic ingredients of laundry detergent products, 445 where the interest lay in determining alkylbenzene sulfonates, alkyl sulfonates, zeolite, phosphate, silicate and sulfate. XRF was also used in the determination of Mn in a dye, FD&C Blue No 1, 446 deposits of aluminium hydroxide and alum±sodium aluminate found in the paper-making process, 447 iodine in iodized salt 448 and wear metals in lubricating oil.…”
Section: Industrialmentioning
confidence: 99%
“…Morel and colleagues 440 evaluated methods for measurement of uranium enrichment by recording emissions from 235 U, 238 U and X-ray ¯uorescence induced within the sample by radiation w100 keV. And ®nally, the role of several techniques, including XRF, in characterizing plutonium for the purposes of international security, stock-pile stewardship and the characterization of mixed oxide fuels were discussed in a conference presentation by Mahan et al 441 XRF has also contributed to an astonishing variety of other industrial applications including: the analysis of drugs; 442 cigarettes widely smoked in Kenya and cigarette ash 443 in which it was reported that signi®cant quantities of As, Ga and Se were ingested during smoking; beauty creams also sold in Kenya, 444 where concern was expressed about the Hg content of some of the samples; anionic surfactants and other inorganic ingredients of laundry detergent products, 445 where the interest lay in determining alkylbenzene sulfonates, alkyl sulfonates, zeolite, phosphate, silicate and sulfate. XRF was also used in the determination of Mn in a dye, FD&C Blue No 1, 446 deposits of aluminium hydroxide and alum±sodium aluminate found in the paper-making process, 447 iodine in iodized salt 448 and wear metals in lubricating oil.…”
Section: Industrialmentioning
confidence: 99%
“…or in water (sodium silicates) and measurement of aluminium and silicon in the solution by gravimetry, titration, flame atomic absorption spectrometry (FAAS), inductively coupled plasma atomic emission spectrometry 1 (ICP-AES) or x-ray fluorescence (XRF) spectrometry. 2 The XRF method using the aqueous detergent solution is time consuming. In this method, the zeolite is filtered as a residue on filter-paper on which aluminium is measured and the filtrate is added dropwise on to a microdroplet filterpaper on which silicon is measured.…”
Section: Introductionmentioning
confidence: 99%